Information transfer in medicine: modus vivendi out of paradise*. (4th March 2013) - Griebenow, Reinhard; Michalis, Lampros; Schulenburg, Dirk; Schaefer, Robert; Weber, Heinz
Abstract : Medical communication constitutes the backbone of acquisition and maintenance of professional competence for physicians. The fact that during recent decades, the vast majority of medical innovations has either been developed by commercial companies or at least been marketed on a commercial basis represents a huge challenge to the freedom of medical communication from commercial bias. This article summarises the current situation regarding bias in medical information transfer and focuses on international CME/CPD activities from the point of view of a European accreditor, the European Board for Accreditation in Cardiology (EBAC).